(untitled) (Zbornik Pravnog fakulteta Sveučilišta u Rijeci, 2022)
In recent times, humanity has experienced the devastating effects of the COVID-19 crisis, which has caused sharp ruptures in different spheres of social life. Detrimental effects of the almost unprecedented crisis have triggered an avalanche of research to explore the phenomenon in focus while conducting scientific investigation that matters. Despite the rapid influx of scholarly articles, recent literature has shown that there is still a remarkable lack of scholarly attention on disasters and their impact on children. While trying to contribute to and address the noted research gap, to the best of the author’s knowledge, this is the first study that explores pathways to violence against children in the time of the COVID-19 pandemic in Croatia with a focus on the national lockdown. The sample consisted of 63 randomly selected police files involving 65 suspects of criminal offences with elements of violence against 108 closely related children at the five police departments centred in Pula, Rijeka, Zagreb, Split and Osijek. In order to “capture” the violence that emerged during the lockdown and was reported after restrictive measures were lifted, a seven-month time frame (March–September, 2020) was implemented as an additional sampling parameter. The study has revealed that most children repeatedly experience multiple forms of violence within the family that are damaging to their health and wellbeing. Infringement of child’s rights was the most prevalent principal offence allegedly committed to the detriment of both boys and girls who were mostly primary-schoolers. Similarly, consistent with previous findings, the study demonstrated that in most cases, alleged abusers are first-time suspected fathers in their 30s with high school education and average financial assets. This calls for future research and the implementation of effective preventive measures to improve family resilience in the face of disasters yet to come.